Developing service marketing through successful involvement of customer - Naveen, - (International research journal of management, IT and social sciences, 2015)
Customer Relationship Management has its roots in service marketing which is based in turn on the formative work of Berry and the IMP. Its purpose is to integrate marketing, sales, and service functions through business process automation, technological solutions and information resources to maximize each customer contact. In this way, service marketing systems facilitate relationships among enterprises, their customers, suppliers, and employees and so provide the technological means to put relationship marketing philosophy into practice. Organizations that fail to keep up with competitor’s service marketing capabilities risk being seriously disadvantaged. However, the use of technology on its own is not sufficient and firms must combine developments in IT with a philosophy that calls for the re-organization of the entire firm around its customers. This shift will not be easily achieved. Our purpose, based on collaborative Canfield/CSC Computer Sciences Corporation studies, is to identify the pitfalls, and offer advice on the successful implementation of service marketing systems in support of relationship marketing strategies, including an audit of the organization’s readiness to proceed.